Comorbidities, Intradialytic Complications and Prescription Pattern among Patients with Chronic Kidney Disease on Maintenance Dialysis at Tertiary Hospital in Tanzania: A Descriptive Cross-Sectional Study (Tanzania Medical Journal, 2025)
BackgroundChronic kidney disease (CKD) is a major public health challenge and a widely prevalent non-communicable disease in both the developed and developing world. Patients with CKD on maintenance dialysis have been shown to present with different comorbidities and hemodialysis-associated complications that make them at risk of multiple drug prescriptions. We investigated comorbidities, hemodialysis-associated complications, and prescription patterns among patients with CKD on maintenance dialysis at a tertiary hospital in Tanzania.MethodsThis was a retrospective cross-sectional study conducted among 180 patients who attended maintenance dialysis service at the Muhimbili National Hospital dialysis unit from 01 January to 30 June 2022. A structured questionnaire was used to collect both sociodemographic and clinical data from the dialysis unit database. Prescription pattern was assessed by arranging medications to their first level of an anatomical main group according to the Anatomical Therapeutic Chemical (ATC) classification system.ResultsA total of 180 patients with CKD on maintenance dialysis were included in this study. The median age of study participants was 52 years (range 23-80 years), with male predominance (75.0%). The most common comorbidities were hypertension (35.2%), anaemia (21.6%), coronary artery disease (21.6%) and diabetes mellitus (12.7%). The major hemodialysis-associated complications observed include fatigue (34.5%), nausea and vomiting (17.9%), and headache (16.0%). Based on the Anatomical Therapeutic Chemical (ATC) classification system, drugs for the cardiovascular system were the most prescribed class of drugs (50.1%) followed by drugs for digestive and metabolic disorders (25.1%) and drugs for blood and blood forming organs (21.2%).ConclusionsThe majority of patients with CKD on maintenance dialysis have comorbidities and present with intradialytic complications. The prevalent comorbidities and complications observed in the study were hypertension and anaemia, and fatigue, nausea, vomiting, and headache, respectively. These findings underscore the critical need for comprehensive management of such patients, with a focus on cardiovascular health, as cardiovascular drugs were the most frequently prescribed.